Religious Moderation in the Thought of Sheikh Mahfudz at-Tarmasi: Contextualization of Hadith for the Indonesian Archipelago - Ujang, Ujang Sahid; Tajul Arifin (al-Afkar, Journal For Islamic Studies, 2025)
This study is motivated by the increasing relevance of religious moderation in the context of Indonesia’s diverse religious and cultural landscape. The need to understand and apply religious values in a moderate and inclusive manner is crucial for maintaining social harmony and preventing religiously motivated conflicts. This research aims to analyze the contributions of Syaikh Mahfudz at-Tarmasi's thoughts on contextualizing hadith, particularly in supporting the principles of religious moderation, and to explore their relevance to the Nusantara society. The study employs a normative approach with descriptive-analytical methods. Data were collected through a literature review of Syaikh Mahfudz's works and other relevant supporting literature. The data were then analyzed qualitatively to identify key themes that promote religious moderation. The findings reveal that Syaikh Mahfudz at-Tarmasi utilized a methodology of sanad and matan criticism in interpreting hadiths. He not only scrutinized the textual authenticity but also considered the social and cultural contexts, resulting in a moderate understanding of Islam that aligns with the pluralistic nature of Indonesian society. The study's findings underscore the necessity of strengthening moderate Islamic preaching based on the values of rahmatan lil ‘alamin to enhance interfaith tolerance and counter extremism. This research is expected to contribute significantly to the enrichment of hadith studies in Indonesia and to offer practical guidance for implementing peaceful and inclusive Islamic teachings within a multicultural society.